Obstacles to Hotel Training among Students of the Department of Hotel and Tourism Sciences at Aqaba University College in Al-Balqa Applied University and Ways to Overcome them (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
Hotel training represents the cornerstone of professional preparation and qualification programs because it helps trainee students to identify the problems of their occupation and adapt gradually to them. Therefore, the study aimed to identify the obstacles to hotel training among students and to examine their proposals to overcome these obstacles and find solutions to them in their attempt to improve the quality of hotel training. The current study is basically interested in improving the quality of hotel training for students of the Department of Hotel and Tourism Sciences by providing feedback to those in charge of hotel training programs highlighting the strengths and weaknesses of their programs and developing suggestions to address the problems facing students of the Department of Hotel and Tourism Sciences during hotel training. The study used the descriptive approach on a sample of 124 hotel training students and associate degree students in the Department of Hotel and Tourism Sciences at Aqaba University College, in Al-Balqa Applied University in the Hashemite Kingdom of Jordan; a questionnaire consisting of three parts was designed to achieve the objective of the study. Several results were reached at in the study, the most important of which are the low financial return in return of the effort exerted by students in training, the lack of necessary skills among students to overcome the problems and strains of training, the lack of financial allocations provided by the college to improve the quality of the hotel training process for students, and poor coordination between the college administration and hotels regarding facilitating the training process for students. The study also advances a set of recommendations for various levels of students, such as increasing the financial allocations for trainees and designing courses or curricula that help students develop their skills in solving training problems they face.
Keywords: Hotel Training-Supervision; Guidance-Training; Development; Hotel Management; Customer Service